Pengaruh Merger Dan Akuisisi (M&A) Terhadap Nilai Perusahaan Sektor Teknologi Informasi Global - Astari, Marsya Yulia (Syntax Literate, 2025)
This study aims to analyze the impact of merger and acquisition (M&A) activities on firm value in the global information technology sector. The research focuses on two types of integration—horizontal and conglomerate—and compares the firm value of companies that underwent M&A to those that did not. The study employs a quantitative approach using the Difference-in-Difference (DID) method and panel data from global IT companies that conducted M&A during 2013–2017, with follow-up observations until 2023. Firm value is measured using the TEV/EBITDA metric, with control variables including Return on Equity (ROE), Debt-to-Equity Ratio (DER), and Firm Size. The results show that M&A has a significant effect on increasing firm value, particularly for horizontal integration compared to conglomerate. Firms engaging in M&A generally show higher value performance than their non-M&A counterparts. This study provides important contributions to strategic corporate decision-making and serves as a reference for investors assessing post-acquisition performance potential.